Flexible Sliding Window - Saidi, Mohamad Hariz; Hood, Khairul Anuar Ridzuan; Adnan, Mohd Fitri; Muhammad Hashim, Mohd Zulfadli; Halim, Nor Syazana; Mohamad Marzuki, Nursyaza Dinie; Abd Karim, Siti Fatma (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Contemporary window designs significantly improve user comfort, safety, and overall convenience, especially for occupants of high-rise buildings. Conventional window systems often present difficulties in terms of limited ventilation and challenging cleaning access, particularly for the elderly, individuals with disabilities, and residents of condominiums. Thus, this project introduces an innovative solution called the Flexible Sliding Window, an automated sliding window that can rotate up to 180°, allowing for easier maintenance and improved airflow. The development process includes several essential stages: conceptualization, 3D modeling using Autodesk Inventor 2016, careful selection of materials like aluminium 6061 and acrylic sheets, machining with computer numerical control (CNC) and traditional machines, and integration of automation elements such as direct current (DC) motors and speed controllers. Prototype testing confirmed that the Flexible Sliding Window functions efficiently and aligns with the intended design criteria. Performance evaluation showed that the system significantly reduces window cleaning time by 3–5 minutes compared to conventional louver-type windows while enabling seamless 180° rotations with controlled speed. Structural analysis conducted through Autodesk Inventor validated the robustness of the design, with aluminium providing excellent strength and corrosion resistance. Project findings revealed that core features, automated operation, complete rotational capability, and user-centered design effectively solve issues related to cleaning and ventilation, offering a reliable and safer alternative. Proposed enhancements for future versions include incorporating rain sensors and utilizing solar power for energy efficiency. This project met its objectives successfully and presents promising potential for use in residential and commercial buildings. The Flexible Sliding Window satisfies modern user demands and demonstrates valuable innovation within the architectural and manufacturing sectors. Future research is encouraged to evaluate long-term functionality, improve child safety features, and explore certification for broader commercialization.